Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Puskesmas Burneh Kabupaten Bangkalan - Septri, Muhti Septriannas; Kuswinarno, mudji (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This research was conducted at the Burneh Health Center Service Employees of Bangkalan Regency. Burneh Health Center is an element of government implementation in the health sector. The human resources contained in it must have good performance to achieve organizational goals. The existing problems are in the performance of employees who have decreased. Some employees also often violate the provisions of working hours that have been determined so that employee discipline and work motivation are getting lower. The low level of employee motivation can be indicated from the lack of leadership both to nurses and doctors as well as to patient families. This study aims to determine the effect of work discipline on employee performance at the Burneh Health Center, Bangkalan Regency, to determine the effect of work motivation on employee performance at the Burneh Health Center, Bagkalan Regency, and to determine the effect of work discipline and motivation on employee performance at the Burneh Health Center, Bangkalan Regency. The method used in this research is quantitative research. The population in this study was 55 employees, so this research is population research. The data collection methods used are through interviews, questionnaires and literature studies. The data analysis techniques used are Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis and Hypothesis Test. The results of this study indicate that, 1) Work Discipline has a positive and significant effect on Employee Performance with a tcount value of 5.771 ttable 1.67591 with a significant level of 0.000 0.05 with a β value of 1.576. 2) Work Motivation has a positive and significant effect on Employee Performance with a tcount value of 2.900 t table 1.67591 with a significant level of 0.006 0.05 with a β value of 0.863. 3) Discipline and Work Motivation have a positive and significant effect on Employee Performance with an Fcount value of 65,173 t table 3.13 with a significant level of 0.000 0.05.